Development and Rasch analysis of the Assessment of Computer-Related Skills. - Fischl C; Fisher AG (Scandinavian Journal of Occupational Therapy, 2007)
The purpose of this study is to evaluate the internal scale validity, person response validity, and reliability of the newly developed Assessment of Computer-Related Skills (ACRS). Data from 32 healthy adult participants who performed two to three computer tasks were analysed to determine how well the participants fitted the many-faceted Rasch (MFR) model of the ACRS, as well as how well the ACRS skill items and tasks (a) fitted the MFR model of the ACRS, (b) matched the expectations for hierarchical ordering of their difficulties, and (c) differentiated persons into different levels of ability. Results indicated that with three skill items removed, the remaining 34 skill items, 8 computer tasks, and 30 participants demonstrated goodness-of-fit to the MFR model of the ACRS. The skills and tasks appeared to have logical hierarchical ordering and differentiated participants into at least three levels of ability. The findings affirmed the internal scale validity, person response validity and reliability of the ACRS for assessing persons' computer abilities. Future studies using a larger sample that includes individuals with disabilities and with difficulties with computer use are needed to further evaluate the validity and reliability of the ACRS.